1968
DOI: 10.1037/h0026506
|View full text |Cite
|
Sign up to set email alerts
|

Emotional meaning of four typographical variables.

Abstract: The influence of 4 typeface variables (angular versus curved, bold versus light, simple versus ornate, serif versus sans-serif) on judgments of emotional meaning was studied in 40 college students. In addition to specific conclusions for each mood, it was found that, in general, moods such as sprightly, sparkling, dreamy, and soaring tend to be matched to curved, light, ornate, and perhaps sans-serif type; while moods such as sad, dignified, and dramatic are matched to angular, bold, and perhaps serif type

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 8 publications
5
37
0
1
Order By: Relevance
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…In the spirit of early empiricists, experimenters manipulated contour using simple stimuli, such as lines or abstract displays composed of curves or angles. The results of these early studies, confirmed later using typography (15), converged to show that curvilinear forms are experienced as softer and more pleasant, whereas angular forms are experienced as harder and more serious.…”
supporting
confidence: 63%
“…Based on their findings, the authors came to the conclusion that the formal attributes having the biggest influence on the subjects' impression are the extreme size, character width and character brightness. Castle and Child [4] found that there is a connection between specific moods and specific variables of typefaces. However, the means of manipulation with the typographic stimuli in the mentioned studies, as well as the divided focus of the researches on multiple goals, reveal a certain confounding of variables which makes it hard to isolate with any certainty the specific, or universal characteristics that contribute to connection with the given attributes.…”
Section: Introductionmentioning
confidence: 99%
“…But research suggests that properties such as uppercase versus lowercase, bold versus light (weight of a typeface), angularity versus roundedness, and serif versus sans serif all play a role (Kastl & Child, 1968;Tannenbaum, Jacobson, & Norris, 1964).…”
Section: Typographic Effectsmentioning
confidence: 98%